Database security and auditing : protecting data integrity and accessibility - Afyouni, Hassan A. (Boston, Mass. : Thomson/Course Technology, 2006)
Designed for easy learning, this text is broken into three sections: security, auditing and implementation. Students will fully understand how to implement database security on modern business databases using practical scenarios and step-by-step examples throughout the text.
Introduction -- pt. 1. Chp. 1. Security Architecture -- Chp. 2. Operating System Security Fundamentals -- Chp. 3. Administration of Users -- Chp. 4. Profiles, Password Policies, Privileges, and Roles -- Chp. 5. Database Auditing Models -- Chp. 6. Virtual Private Databases -- pt. 2. Chp. 7. Data Auditing Models -- Chp. 8. Application Data Auditing -- Chp. 9. Auditing Database Activities -- pt. 3. Chp. 10. Security and Auditing Project Cases.
Includes index.
1 2
Keywords: Database security; Database management